Halloysite nanotubes loaded with alkyl trimethyl ammonium bromide as antibacterial agent for root canal sealers. Issue 5 (May 2019) - Monteiro, Juliana Caletti; Garcia, Isadora Martini; Leitune, Vicente Castelo Branco; Visioli, Fernanda; de Souza Balbinot, Gabriela; Samuel, Susana Maria Werner; Makeeva, Irina; Collares, Fabrício Mezzomo; Sauro, Salvatore
Highlights: Endodontic sealer was formulated with nanotubes and an antibacterial agent. The physical-chemical properties of sealers were not affected. The sealers have no evident cytotoxicity in human pulp fibroblasts. The sealers showed high antibacterial activity against Enterococcus Faecalis . Abstract: Objective: This study aimed at evaluating the effects of experimental endodontic sealers containing halloysite nanotubes (HNT) doped with alkyl trimethyl ammonium bromide (ATAB). Methods: An experimental dual-cure resin sealer was formulated and used as control material. This resin was also filled with ATAB and HNT at different ratios (GATAB:HNT 1:1; 1:2; 2:1) generate three experimental resin sealers. The ATAB:HNT filler was characterized through transmission electron microscopy (TEM). While, the experimental and control sealers were evaluated for degree of conversion, softening ration, radiopacity, flow, film thickness, antibacterial activity for biofilm and planktonic bacteria and cytotoxicity in human pulpal cells. Results: GATAB:HNT(1:1) significantly increased the immediate DC (p < 0.05), although no difference was encountered between the groups after 24 h (p > 0.05). All the experimental cements (ATAB/HNT) showed relatively low initial Knoop hardness (p < 0.05), but with no significant reduction (p > 0.05) after storage in ethanol (softening ratio). The radiopacity of all groups achieved at least 3 mm of aluminum. All groups showed more than 17 mm of flow, with a film thickness lower than 50 μm (ISO 6876:2012). All the experimental ATAB:HNT cements showed antibacterial activity against E. faecalis; the higher the ATAB ratio, the greater the antibacterial activity (p < 0.05). Cell viability was higher than 70% with no significant difference between the groups (p > 0.05). Significance: The incorporation of ATAB/HNT into the experimental resin sealers induced antibacterial activity against biofilm and planktonic E. faecalis without affecting the pulp cell viability or the chemo-mechanical properties.